Sleep restriction exacerbates cardiac dysfunction in diabetic mice by causing cardiomyocyte death and fibrosis through mitochondrial damage - Jingyi Zhang; Xu Zhao; Jing Tang; Ce Liu; Yining Zhang; Cheng Cai; Qingfeng Du (Cell Death Discovery)
Abstract Diabetic cardiomyopathy (DCM) is a cardiovascular complication of diabetes mellitus with a poor prognosis and is the leading cause of death in diabetic patients. Sleep deficiency is not only recognized as an important risk factor for the development of type 2 DM, but is also associated with increased morbidity and mortality of cardiovascular disease. The underlying role and mechanisms of sleep restriction (SR) in DCM are far from clear. The KK/Upj-Ay mouse model of T2 DM was used as a study subject, and the small animal ultrasound imaging system was used to detect the function of the heart; immunopathological staining was used to clarify the histo-structural pathological alterations of the heart; and TUNEL staining, qPCR, transmission electron microscopy (TEM), and ELISA kits were used to detect apoptosis, oxidative stress, inflammation, and mitochondrial damage, and related molecular alterations. SR led to a significant increase in mortality, cardiac hypertrophy, necrosis, glycogen deposition and fibrosis further deteriorated in DM KK mice. SR increased cardiomyocyte death in KK mice through the Bax/Bcl2 pathway. In addition to this, SR not only exacerbated the inflammatory response, but also aggravated mitochondrial damage and promoted oxidative stress in KK mice through the PRDM16-PGC-1α pathway. Overall, SR exacerbates structural alterations and dysfunction through inflammation, oxidative stress, and apoptosis in DM KK mice, increasing the risk of death. Clinicians and diabetic patients are prompted to pay attention to sleep habits to avoid accelerating the transition of DCM to heart failure and inducing death due to poor sleep habits.